Towards a National Food Pulse Strategy: The role of public policy in unlocking the potential of pulses in England's agri‐food system - Lucy Michaels; Rosanne Maguire; David Barling (Annals of Applied Biology, 2026)
Abstract Despite recognised agronomic, environmental, and nutritional benefits, English pulse production and consumption remain limited, constrained by locked‐in cereal rotations, limited farmer know‐how and processing infrastructure, and weak consumer demand. This Policy Forum paper aims to support ongoing discussion of the role public policy could play in enabling the expansion of domestically grown food pulses in England, examining the current policy, research and market landscape, systemic opportunities, food‐system trade‐offs, and potential ways forward. Matrix analysis was employed to facilitate structured comparison and synthesis of academic literature, policy documents, and semi‐structured expert interviews ( n = 13). Analysis identifies no direct policy support for food pulse production in England and a fragmented, under‐resourced research landscape. International examples highlight different, albeit context‐specific, public policy drivers including production incentives, support for translational research, value‐chain coordination and demand measures. Potential public policy interventions identified for England range from subsidies and R&D investment to infrastructure support and knowledge exchange, market coordination, and greater policy coherence. Food pulse production in England remains marginal because it requires a coupled production–consumption transition. Progress is further complicated by disagreements over priorities, desired outcomes, and the level of state support and market intervention necessary. The paper identifies routes beyond this impasse, including sequencing feed and food markets to support infrastructure and demand formation and enabling parallel agroecological and commodity‐scale pathways. It also highlights the need for greater coordination of policy, research and innovation, involving stakeholders across government, the value chain and wider society.